Association between metabolic syndrome and gingival inflammation in obese children. Issue 3 (10th November 2017) - Kâ, K; Rousseau, M‐C; Tran, SD; Henderson, M; Nicolau, B
Abstract: Background and objective: Our previous work showed a positive association between metabolic syndrome (MetS) and gingival crevicular fluid (GCF) tumour necrosis factor‐alpha (TNF‐α) in a sample of obese and non‐obese children. However, whether this association persists among obese children is unknown. We aim to investigate the extent to which MetS is associated with GCF TNF‐α level among obese children. Methodology: We performed a cross‐sectional analysis using data from visit 1 of the QUebec Adipose and Lifestyle InvesTigation in Youth cohort. A total of 219 obese children aged 8‐10 years, for whom data were available for both MetS and TNF‐α, were included in our analysis. The independent variable, MetS, was defined according to the International Diabetes Federation recommendations. GCF samples were collected from the gingival sulcus using a paper strip, and the concentration of TNF‐α was determined by enzyme‐linked immunosorbent assay. Analyses included descriptive statistics and sex‐specific linear regression analyses adjusting for potential confounders. Results: In this sample comprising only obese children, 24 (10.9%) had MetS. Among obese boys, those with MetS had 44.9% higher GCF TNF‐α (95% confidence interval: 16.5%‐73.3%) compared to those without MetS. No such association was detected in obese girls. Conclusion: MetS was positively associated with GCF TNF‐α concentration in obese boys. These results suggest that obese boys with MetS may have a worse gingival health profile compared to their obese counterpart without MetS.